Mono-Locus and Pyramided Resistant Grapevine Cultivars Reveal Early Putative Biomarkers Upon Artificial Inoculation With Plasmopara viticola - Ciubotaru, Ramona Mihaela; Franceschi, Pietro; Zulini, Luca; Stefanini, Marco; Škrab, Domen; Rossarolla, Marcia Denise; Robatscher, Peter; Oberhuber, Michael; Vrhovsek, Urska; Chitarrini, Giulia (Frontiers in Plant Science, 2021)
One of the most economically important grapevine diseases is Downy mildew (DM) caused by the oomycete Plasmopara viticola. A strategy to reduce the use of fungicides to compensate for the high susceptibility of V. vinifera is the selection of grapevine varieties showing pathogen-specific resistance. We applied a metabolomics approach to evaluate the metabolic modulation in monogenic-resistant genotypes (BC4, Bianca, F12P160, Solaris), as well as in pyramided-resistant genotypes (F12P60 and F12P127) taking as a reference the susceptible genotype Pinot Noir. In order to understand if different sources of resistance are associated with different degrees of resistance and, implicitly, with different responses to the pathogen, we considered the most important classes of plant metabolite primary compounds, lipids, phenols and volatile organic compounds at 0, 12, 48 and 96 hours post artificial inoculation (hpi). We identified 264 modulated compounds; among these, 22 metabolites were found accumulated in significant quantities in the resistant cultivars compared to Pinot Noir. In monogenic genotypes, the highest modulation of the metabolites was noticed at 48 hpi and 96 hpi, except for Solaris, that showed a behavior similar to the pyramided genotypes in which the changes started to occur as early as 12 hpi. Bianca, Solaris and F12P60 showed the highest number of interesting compounds accumulated after the artificial infection and with a putative effect against the pathogen. In contrast, Pinot Noir showed a less effective defense response in containing DM growth.